Polyclonal B‐cell lymphocytosis: Report of three cases. Issue 6 (24th May 2018) - Marcondes, Natália Aydos; Schneider, Laiana; Spindler, Bianca Michel; Fernandes, Flavo Beno; Faulhaber, Gustavo Adolpho Moreira
Abstract : Background: Persistent polyclonal B‐cell lymphocytosis (PPBL) is a rare benign condition characterized by a polyclonal B‐cell lymphocytosis with binucleated lymphocytes. We hereby report three cases of PPBL. Methods: Flow cytometry immunophenotyping was performed in peripheral blood samples from three patients with clinical suspicion of lymphoproliferative disease. Results: Case 1 was a female middle‐aged smoker; Case 2 was an elderly male; and Case 3 was a non‐smoker female. Flow cytometry evaluation of all cases revealed an expansion of mature B‐cells, with a normal Kappa/Lambda light chain ratio; B‐cell lymphocytes of Cases 2 and 3 had CD5 coexpression; Case 3 also had monocytosis. Conclusions: Diagnose of PPBL is important in order to avoid unnecessary diagnostic procedures and therapy. © 2018 International Clinical Cytometry Society